Modification of SiO2 from Rice Husk with Polyvinyl Alcohol (PVA) as Adsorbent of Congo Red Dye - Robert Sibarani; Abdullah Abdullah; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Rice husk is an agricultural waste abundant in silica (SiO₂). SiO2 extracted from rice husk has a porous structure, so it has the potential to be used as an adsorbent material. To increase the stability and effectiveness of the adsorption process, SiO2 was modified by adding Polyvinyl Alcohol (PVA) and used to removal Congo red dye. SiO₂ extraction was carried out through a calcination process at three different temperatures, namely 600, 700, and 800 °C. Morphological analysis and elemental composition using SEM-EDX showed the presence of a polymer layer on the surface of the material, which functions as a distribution medium for SiO₂ particles. In addition, an increase in carbon (C) content was detected after the addition of PVA, confirming the presence of PVA in the composite. The optimum conditions for the adsorption process of Congo red dye by SiO₂-PVA were obtained at pH 1, contact time 75 minutes, and solution concentration 75 mg/L. Experimental data showed that the Langmuir isotherm model was most suitable for describing adsorption behavior compared to the Freundlich model, with an adsorption capacity of 14.31 mg/g. These results indicate that SiO₂-PVA has the potential as an alternative adsorbent for the treatment of waste containing dyes.